Rapid and gradual modes of aerosol trace metal dissolution in seawater - Mackey, Katherine R. M.; Chien, Chia-Te; Post, Anton F.; Saito, Mak A.; Paytan, Adina (Frontiers in Microbiology, 2015)
Atmospheric deposition is a major source of trace metals in marine surface waters and supplies vital micronutrients to phytoplankton, yet measured aerosol trace metal solubility values are operationally defined and there are relatively few multi-element studies on aerosol-metal solubility in seawater. Here we measure the solubility of aluminum (Al), cadmium (Cd), cobalt (Co), copper (Cu), iron (Fe), manganese (Mn), nickel (Ni), lead (Pb), and zinc (Zn) from natural aerosol samples in seawater over a 7 day period to (1) evaluate the role of extraction time in trace metal dissolution behavior and (2) explore how the individual dissolution patterns could influence biota. Dissolution behavior occurs over a continuum ranging from rapid dissolution, in which the majority of soluble metal dissolved immediately upon seawater exposure (Cd and Co in our samples), to gradual dissolution, where metals dissolved slowly over time (Zn, Mn, Cu, and Al in our samples). Additionally, dissolution affected by interactions with particles was observed in which a decline in soluble metal concentration over time occurred (Fe and Pb in our samples). Natural variability in aerosol chemistry between samples can cause metals to display different dissolution kinetics in different samples, and this was particularly evident for Ni, for which samples showed a broad range of dissolution rates. The elemental molar ratio of metals in the bulk aerosols was 23,189Fe: 22,651Al: 445Mn: 348Zn: 71Cu: 48Ni: 23Pb: 9Co: 1Cd, whereas the seawater soluble molar ratio after 7 days of leaching was 11Fe: 620Al: 205Mn: 240Zn: 20Cu: 14Ni: 9Pb: 2Co: 1Cd. The different kinetics and ratios of aerosol metal dissolution have implications for phytoplankton nutrition, and highlight the need for unified extraction protocols that simulate aerosol metal dissolution in the surface ocean.